Standard Operating Procedure Preservasi Koleksi di Perpustakaan (Studi Kasus di Perpustakaan Universitas Sarjanawiyata Tamansiswa Yogyakarta) - Batriatul Alfa Dila (Pustabiblia: Journal of Library and Information Science, 2020)
Implementation of information retrieval activities in a library is inseparable from the work role of the librarian, for that in a library there needs to be a written policy regarding standard operating procedures for preservation of collections in the library. This research traced information based on standard library procedures regarding collection development policies based on legal standards or preservation SOP policies, with qualitative research methods with the Snowball Sampling technique. The results of this study indicate that in the UST library has not implemented standard operating procedures in preservation collection activities, this is reflected in the process of preservation activities do not have a preservation SOP that is based on the legal basis for preservation of the collection as stated in the SOP document control contained in SOP No. 001.002 / ot 01 01 / isn 6, Law Number 13 of 2018 concerning transfer of printed and recorded works, Regulation of the Head of the National Library Number 16 of 2014 concerning procedures for storing and using special collections and SNI 7330: 2009 for Higher Education libraries.